Research on the Mechanism and Affect of Recommendation Marketing from the Perspective of AIDMA Theory - Liu, Yakun; Song, Yifei (Economics & Management Review, 2022)
Looking back at the outbreak of the COVID-19 in the past few years, although China’s real economy has been hit hard, the online economy has achieved unprecedented development. To some extent, the epidemic has promoted the rapid shift of consumption demand from offline to online. At the same time, with the development of Internet technology, online shopping and social communication have become the normal life of people, and users’ consumption habits and preferences have also changed. 70% of the post-1995 consumers are keen on the consumption mode of “being recommended first, purchase goods second”. This paper will start from the theory of AIDMA to explore the mechanism and effect of recommendation marketing in the post-epidemic era.